Social cohesion teaching approach: a meta-analysis exploritory research - Siti Aisyah Mat Saad; Anuar Ahmad; Ruhizan Mohd. Yassin; Musirin Mosin (Pennwell Corporation, 2020)
Malaysia is made up of various races with different cultures, religions and beliefs. Because of that, unity and peace is an important aspect within a country which needs to be supported and backed by the education system to ensure stability in all aspects such as politics, economy as well as social. This research aims to figure out an approach that can give birth to social cohesion among students and analyze the teaching approach that can lead to social cohesion. Next, this research looks at social cohesion and its importance in teaching approaches at schools. This research also discusses past studies that have been carried out on the social cohesion approach in subjects such as Science, History, Integrated Life Skills, Mathematics, general studies and humanities.